The state policy of service sector development in the Republic of Kazakhstan - Zhunussova, Assel Zhumaevna; Dulambayeva, Raushan Tlegenovna (Journal of Eastern European and Central Asian Research (JEECAR), 2019)
Scientific-methodical approaches of identifying the main factors for attracting deposits in the Ukrainian banking system are presented in this paper. The author offers the following procedure: a comparative analysis of the long-term dynamics (2000–2017) of the placement of deposits in Ukrainian, Belarussian, and Polish banking systems as a result of socio-economic development trends in these countries; an estimation at the macroeconomic level of the factors influencing this process, using methods of principal components analysis and factors classification; and detection of regression-correlating dependencies between the grouping variable (deposit volume) and variables of analysis through the sample regression function identification for these countries. The theory that attraction of deposits to the Ukrainian banking system was turbulent due to both the insufficient development of other financial market institutions and the prudent behavior of national economy agents is substantiated. Activation of bank deposit activity was found to be connected with measures of demographic situational improvements, thus ensuring the economic freedom of business entities in a hybrid war with the Russian Federation.